2013
DOI: 10.1038/srep02424
|View full text |Cite
|
Sign up to set email alerts
|

Colour and odour drive fruit selection and seed dispersal by mouse lemurs

Abstract: Animals and fruiting plants are involved in a complex set of interactions, with animals relying on fruiting trees as food resources, and fruiting trees relying on animals for seed dispersal. This interdependence shapes fruit signals such as colour and odour, to increase fruit detectability, and animal sensory systems, such as colour vision and olfaction to facilitate food identification and selection. Despite the ecological and evolutionary importance of plant-animal interactions for shaping animal sensory ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 41 publications
0
62
1
1
Order By: Relevance
“…Although the bats used a wide source of the fruits of the Malpighiaceae, Poligonaceae, Boraginaceae, Anacardiaceae, Combretaceae and Sapindaceae families; other studies have registered the preference of the Urticaceae, Moraceae, Piperaceae and Solanaceae families (Lou and Yurrita, 2005;Da Silva et al, 2008;Novoa et al, 2011). This may suggest that the penetrating odors expelled by the fruits of the families above mentioned promotes and facilitates their location (Valenta et al, 2013). An important fact is that diversity of plants found in the bats diet was smaller (11 plant species), unlike what has been observed in studies with 19 (GalindoGonzález, 1998) and 22 (Novoa et al, 2011) species of bats.…”
Section: Seed Handlingcontrasting
confidence: 49%
“…Although the bats used a wide source of the fruits of the Malpighiaceae, Poligonaceae, Boraginaceae, Anacardiaceae, Combretaceae and Sapindaceae families; other studies have registered the preference of the Urticaceae, Moraceae, Piperaceae and Solanaceae families (Lou and Yurrita, 2005;Da Silva et al, 2008;Novoa et al, 2011). This may suggest that the penetrating odors expelled by the fruits of the families above mentioned promotes and facilitates their location (Valenta et al, 2013). An important fact is that diversity of plants found in the bats diet was smaller (11 plant species), unlike what has been observed in studies with 19 (GalindoGonzález, 1998) and 22 (Novoa et al, 2011) species of bats.…”
Section: Seed Handlingcontrasting
confidence: 49%
“…These mammals occur throughout Madagascar and have radiated to fill a unique variety of life history and dietary niches (1)(2)(3). For example, it has been noted that compared with other tropical biomes, Madagascar is depauperate in seed dispersers, with lemurs (the primates of Madagascar) acting as the predominant dispersers (4)(5)(6)(7)(8). Despite their importance as seed dispersers of native plants, living Malagasy primates comprise proportionately fewer frugivores than comparable primate assemblages on other continents, with a higher than expected proportion of lemurs eating predominantly leaves (8,9).…”
mentioning
confidence: 99%
“…Algunos estudios han demostrado que ciertas características de las plantas como el tamaño y peso del fruto sirven como señales críticas para la atracción de dispersores (Alcántara & Rey, 2003;Valenta et al, 2013). Acorde con Willson y Traveset (2000), la variación en las características morfométricas como el peso del fruto, el peso de arilos, así como el número y peso de semillas pueden tener efecto en la dispersión.…”
Section: Site Of Studyunclassified
“…Some studies have shown that certain characteristics of plants, such as size and weight of the fruit, serve as critical signals to attract dispersers (Alcántara & Rey, 2003;Valenta et al, 2013). According to Willson and Traveset (2000), the variance in the morphometric characteristics, such as weight of the fruit and weight of the arils, as well as the number and weight of the seeds, can have an effect on the dispersal.…”
Section: Introductionmentioning
confidence: 99%